ANALYSIS OF MODES AND DIAGNOSTICS OF POWER KEYS OF CONTROL SYSTEMS OF ASYNCHRONOUS DRIVES OF ELECTRIC LOCOMOTIVES OF ALTERNATING CURRENT - Yakubov M.S; Sagatova M.A (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article presents the results of the analysis of the technical condition of IGBT power switches used in control systems of modern AC electric locomotives under operating voltage when driving under various actions of overcurrent, voltage, overheating and short circuits leading to their failure.